2009
DOI: 10.1007/s10745-009-9226-5
|View full text |Cite
|
Sign up to set email alerts
|

Scale Dependency and the “Marginal” Value of Labor

Abstract: While there is a general assumption that labor has a positive effect on pastoral production, studies that have tried to quantify this relationship have found no effects. This is most likely because these studies have been looking for effects only at the household level of social organization, although it is well documented that nomadic pastoralist households share and exchange labor in socalled cooperative herding groups. This study investigates possible labor related effects on production among Saami reindeer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…The positive relationship between pre- and post-collapse herd size indicates that herd accumulation is a rational response to environment-induced catastrophes, and provides the rationale for why both reindeer herders [29], [31] and pastoralists in general [39] invest labour to increase herd size. Nevertheless, herd accumulation may also stem from cultural values: e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The positive relationship between pre- and post-collapse herd size indicates that herd accumulation is a rational response to environment-induced catastrophes, and provides the rationale for why both reindeer herders [29], [31] and pastoralists in general [39] invest labour to increase herd size. Nevertheless, herd accumulation may also stem from cultural values: e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For the reindeer husbandry it has been demonstrated that reindeer density and climatic conditions have negative effects on individual body mass [12], [31], [48], [49], [50] and, consequently, also survival [49], [51]. Increased reindeer abundance also increases herders’ vulnerability to unfavourable climate as the negative impacts of adverse climatic events increases with increasing reindeer density [12], [49], [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The size of the siida affects the nature of collective action within the group as well as the group’s productivity/long-term viability. Siidas with more members are likely to have larger herds (Næss et al 2009), which helps to prevent land-grabs from competing groups. Although this is less of a worry given the current trend towards privatised and fenced land, pastoralists still face the task of preventing unwanted encroachment.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, while predation may reduce the profitability of raising livestock, or at least the profitability of increasing herd size (Bulte and Rondeau 2005) as livestock owners have to invest resources in order to be able to increase their herd size (Næss et al 2010; Næss et al 2009), “[w]ith the risk of predation covered by compensation, it is optimal to increase the stocking rate” (Bulte and Rondeau 2005:17).…”
Section: Introductionmentioning
confidence: 99%